Sustainable product design: A life-cycle approach. (18th May 2020) - Zhang, Xiang; Zhang, Lei; Fung, Ka Yip; Bakshi, Bhavik R.; Ng, Ka Ming
Highlights: New sustainable product design framework incorporating rule-based and model-based methods. Life cycle sustainability assessment is incorporated into optimization to offer a comprehensive view of sustainability. Ingredient, manufacturing process, and end-of-use process are determined from the life-cycle perspective for sustainability. Two case studies: composite bumper beam and lithium ion battery. Abstract: A systematic framework is proposed for sustainable chemical product design. The product technical requirements are first identified as design constraints. Then, a base-case product is generated as a reference on top of which a more sustainable product is designed. To do so, the life cycle of base-case product (in particular, whether and how it should be recycled) is decided by using life cycle sustainability assessment (LCSA) or rule-based methods depending on the availability of life cycle inventory data. In addition, the hotspots (i.e., life cycle stages with major impact) are identified. Afterwards, to reduce the impact on hotspots, product design targets and design alternatives are generated using knowledge-base and heuristics. Lastly, LCSA or rule-based methods is applied to decide the most sustainable product from the generated product design alternatives. Two case studies – composite bumper beam and lithium ion battery – are provided to illustrate the framework.